Risk Factor of Child Diarrhea in Indonesia: A Systematic Review - Muhammad Faza Soelaeman; Fabiola Cathleen; Christine Lieana (Cermin Dunia Kedokteran, 2023)
Bakcground: Diarrhea is the leading cause of death among children worldwide, including in Indonesia. However, there is no scientific research on the most common risk factors for diarrhea among children in Indonesia. A systematic literature review was conducted to highlight the most predisposing risk factors of diarrhea based on the epidemiological triangle, in order to improve preventive measures by society to reduce the incidence of childhood diarrhea. Methods: A systematic review of observational studies without limitation of year of publication was performed in 2023 based on PRISMA protocol. Results: A total of 2607 studies were identified from the Pubmed database, only 9 studies were extracted and assessed using the STROBE method. The risk factors were divided into 3 categories: environmental, host and other, to follow the rule of the epidemiologic triangle of disease. The highest odds ratios were found for the factor "child defecation in open places" (OR=10.47) from the environmental category and for the factor "child eating by hand" (OR=5.6) from the host category. Lower maternal education from the host category was also influential (OR=1.52). Conclusion: Improper public disposal of child feces, child behavior of eating with hand and low maternal education are the most significant contributing risk factors of child diarrhea in Indonesia.